2015
DOI: 10.1108/rr-07-2014-0185
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of core full text coverage in CINAHL Complete, ProQuest’s Nursing and Allied Health Source and Lippincott Wilkins and Wilson’s Nursing & Health Professionals Premier Collection

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Studies were found via a systematic search of four databases: MEDLINE, PsycINFO, CINAHL and ProQuest Nursing and Allied Health Source (PNAHS). Whilst CINAHL covers the majority of peer-reviewed papers related to a clinical CSU population, PNAHS holds unique articles not covered in other medical databases [ 14 ]. This database includes studies related to alternative and complementary medicine and rehabilitation professions that consider additional psychosocial factors that may be potentially relevant for this review.…”
Section: Methodsmentioning
confidence: 99%
“…Studies were found via a systematic search of four databases: MEDLINE, PsycINFO, CINAHL and ProQuest Nursing and Allied Health Source (PNAHS). Whilst CINAHL covers the majority of peer-reviewed papers related to a clinical CSU population, PNAHS holds unique articles not covered in other medical databases [ 14 ]. This database includes studies related to alternative and complementary medicine and rehabilitation professions that consider additional psychosocial factors that may be potentially relevant for this review.…”
Section: Methodsmentioning
confidence: 99%